Profitability and resource use efficiency of maize seed production in Palpa district of Nepal (SAARC Journal of Agriculture, 2018)
The study aimed to analyze profitability and resource use efficiency of maize seed production in Palpa district of Nepal. Raosoft Inc. software was used to determine the sample size of 182 maize seed producers from the total 260 maize seed producers in the district. Data was collected using a pre-tested semi-structured questionnaire survey administered to the randomly selected samples. Results showed that the uses as well as cost of major inputs such as seed, labor, farmyard manure (FYM),and management/other cost including tillage were higher among small scale farmers compared to the large scale farmers. The average cost of production among small scale farmers was NRs. 94,195per hectare compared to NRs. 64,145among large scale farmers. A benefit cost ratio of maize seed production was higher for large scale farmers (1.12), which in case of small scale farmers was less than 1, i.e. 0.9. Hence, maize seed production was found profitable only for large scale farmers. Resource use efficiency analysis showed FYM, tillage and labor were overused. This suggests that the use of FYM, tillage and labor should be decreased by 665, 456 and 68 percent respectively. Similarly, cost on seed, chemical fertilizer and management/other were underused, hence, need to increase by 92, 69 and 97 percent respectively for the optimum allocation of resources. Overall, maize seed production is profitable but resources should be optimally utilized and should be carried on larger scale.SAARC J. Agri., 16(1): 157-168 (2018)